Competitive advantages as a complete mediator variable in strategic resources, dynamic capabilities and performance relations in the car sales sector - Navarro García, Antonio (2018)
Taking the resource-based view –RBV- and the dynamic capability view –DCV- as an orientation, the main aim of this study is to develop the mediator role that competitive advantages play in the relations between strategic resources, dynamic capabilities and performance. The study takes place in a dynamic and changing sector: the sale of new cars in Portugal. The results show that (a) achieving competitive advantages, which are decisive for business results, depends on the available strategic resources and the generating of dynamic capabilities, (b) in dynamic and changing sectors strategic resources are essential to generate dynamic capabilities, (c) firms must center their attention on, more than results, the generating of sustainable competitive advantages as these act as a mediator variable of the effect of strategic resources and dynamic capabilities on performance. The data scrutiny uses structural equation modeling (SEM) through PLS as the statistical instrument. The sample comprises 89 firms which sell new cars in Portugal.